'Quasi-isostructural polymorphism' in molecular crystals: inputs from interaction hierarchy and energy frameworks. Issue 10 (23rd December 2015) - Dey, Dhananjay; Thomas, Sajesh P.; Spackman, Mark A.; Chopra, Deepak
Abstract : The polymorphs of ( Z )-2-fluoro- N ′-phenyl benzamidamide with multiple Z ′ form "equi-energetic" crystal structures and exhibit "quasi-isostructurality". Abstract : The polymorphs of ( Z )-2-fluoro- N ′-phenyl benzamidamide with multiple Z ′ produce quasi-isostructural supramolecular architectures, wherein C–H⋯F interaction plays a significant role. The energy framework analysis indicates 2D structural similarities in the interaction topologies of these crystalline forms. The results point to a unique class of 'quasi-isostructural polymorphs' which are nearly equi-energetic crystal structures exhibiting high degrees of similarity in physical properties.